2020
DOI: 10.1055/a-1073-7977
|View full text |Cite|
|
Sign up to set email alerts
|

Pelvic Floor Muscle Training in Female Athletes: A Randomized Controlled Pilot Study

Abstract: The aim of this study was to investigate the effects of pelvic floor muscles training in elite female volleyball athletes and whether it is an effective therapy for stress urinary incontinence. Fourteen athletes, both continent and incontinent, between 18 and 30 years of age, were randomly assigned to an experimental group or a control group. The experimental group received a protocol for pelvic floor muscle training for 4 months. This consisted of three phases: awareness/stabilization, strength training and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 25 publications
0
64
0
1
Order By: Relevance
“…26 Interestingly, although athletes have stronger PFMs, high-quality research demonstrated that after 16 weeks of PFM training, volleyball athletes showed a significant improvement in maximum voluntary PFM contraction and urinary loss. 27 The present study also revealed that although the athletes had a higher maximum voluntary PFM contraction, they could not maintain the contraction strength for a long time (endurance). This leads us to believe that the occurrence of UI during sports training may be due to the difficulty of maintaining prolonged PFM contractions, fatiguing these muscles and leading to urine loss.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…26 Interestingly, although athletes have stronger PFMs, high-quality research demonstrated that after 16 weeks of PFM training, volleyball athletes showed a significant improvement in maximum voluntary PFM contraction and urinary loss. 27 The present study also revealed that although the athletes had a higher maximum voluntary PFM contraction, they could not maintain the contraction strength for a long time (endurance). This leads us to believe that the occurrence of UI during sports training may be due to the difficulty of maintaining prolonged PFM contractions, fatiguing these muscles and leading to urine loss.…”
Section: Discussionmentioning
confidence: 49%
“…Their findings also revealed that mild‐to‐moderate physical activities, such as walking, decrease the risk of UI; however, female athletes are approximately three times more likely to have UI compared to control participants 26 . Interestingly, although athletes have stronger PFMs, high‐quality research demonstrated that after 16 weeks of PFM training, volleyball athletes showed a significant improvement in maximum voluntary PFM contraction and urinary loss 27 …”
Section: Discussionmentioning
confidence: 98%
“…Phasic contraction provides immediate support to the urethra, whereas tonic contraction stabilizes the urethra [27]. An observational study conducted in 2020 demonstrated SUI improvement in athletes that underwent pelvic muscle training compared to those that did not [36]. Furthermore, a pilot study done in 2012 showed an improvement in the vaginal resting pressure and MVC in athletic students who completed an eight-week program of PFM training [37].…”
Section: Non-pharmacological Methodsmentioning
confidence: 99%
“…The various randomized clinical studies returned by the PubMed searches showed the effectiveness of PF rehabilitation in UI [ 12 , 13 , 14 ]. Symptoms of PF dysfunctions may progress and affect an athlete’s life [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a series of sports were found, such as gymnastics, basketball, tennis, field hockey, track, swimming, volleyball, softball, golf (transversal study by Nygaard in 1994 [ 30 ]); female soccer (clinical case by Louis in 2019 [ 13 ]); some cases of female volleyball players (randomized trial by Pires in 2020 [ 14 ]); and elite female athletes (transversal studies by Nygaard in 1996 [ 32 ]) and Thyssen [ 24 ]) and meta-analysis by Cerruto in 2019 [ 35 ]) where the risk of urinary incontinence was shown to be higher in athletes than in the control group, and where physiotherapy favored the control group more than the athletes. This finding is especially interesting given the poor prognosis associated with these sports.…”
Section: Discussionmentioning
confidence: 99%